KAJIAN PENGELOLAAN LAHAN SUBDAS SECANG, KULONPROGO, YOGYAKARTA - , JONATHAN REZA P, Prof. Dr.Suratman Worosuprojo, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aims of this research are to evaluate land capability, to arrange land use direction and to research land management in Secang Sub Watershed. The selection of Secang Sub Watershed as an object of the study is that the area topography landform composed of configuration process denudational, structural, fluvial origin landform and it has the zoning in the form of lower zone, middle zone and upper zone. The method used in this research is purposive area sampling at 48 land units. The land management of Secang Sub Watershed was used approach of land capability evaluation and land use direction. The analysis of land capability use macthing method between land unit characteristic and land capability class criteria. The land unit formed by the overlay from landform, slope, land use and soil which were determined by the land unit characteristics taken from field survey and laboratory analysis. The analyis of land use direction was determined by slope scoring, soil erodibility and avarage daily rainfall. This research has shown that the land capability of Secang Sub Watershed consisted of land class I at 187 ha or 5%, land class II at147 ha or 3,9%, land class III at 515,2 ha or 13,7%, land class IV at 1522,7 ha or 40,6%, land class V at 7,3 ha or 0,2% and land class VI at 1223,2 ha or 32,6%. The land use direction of Secang Sub Watershed was in the form of wetland agriculture at 326,85 ha or 8,71%, settlement and annual crop cultivation area at 200,55 ha or 5,35%, dry land crop cultivation area at 525,81 ha or 14,02%, perennial crop cultivation area at 1981,31 ha or 52,82% and buffer zone at 716,54 ha or 19,10%. The land management in Secang Sub Watershed gives land utilization orientation shows that: lower zone as discharge area in the form of irrigation agriculture, settlement area, livestock, annual crop cultivation and dry land crop cultivation. The middle zone was used for settlement, dry land crop cultivation, agroforestry and buffer forest. The upper zone as recharge area for buffer forest, reservoir, agroforestry, preserve, spring protection and dry land crop cultivation.